Prinsip Appeal Karakter Nussa Dan Rara Pada Serial Animasi Nussa: Analisis Hubungan Simbolik Dan Paradigmatik - Fatihah Izzati Shifwah Najiah; Nevlin Cresentia Herwina; Restu Ismoyo Aji (Jurnal Ilmiah Wahana Pendidikan, 2023)
This paper aims to review the Appeal principles of Nussa and Rara characters in the Nussa animated series through the analysis of symbolic and paradigmatic relationships. Nussa is an animated series produced by The Little Giantz and 4stripe Productions. This animated series raises the genre of children's education and the da'wah of Islam. The main characters in this animation are two siblings. The boy named Nussa and his sister named Rara. This research uses descriptive qualitative methods. From the analysis it was revealed that the two met the Appeal principle which was one of the twelve animation principles. From the analysis it was revealed, the symbolic relationship in the visual aspect, ranging from the attributes, clothing, and physical design of the character with the values that were agreed as a symbol of Islam in society. The symbolic relationship can be seen from the paradigmatic relationship or in absentia from both characters, where the selection of certain visual aspects will have an impact on the symbolic meaning.